PELATIHAN PRESENTASI ILMIAH UNTUK MENINGKATKAN DAYA SAING DALAM KOMPETISI ILMIAH BAGI ANGGOTA EKSTRAKURIKULER KARYA ILMIAH REMAJA DI KOTA SEMARANG - Santi Pratiwi T.U.; Deby Luriawati Naryatmojo (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
The quality of human resources will increase with the mastery of science and technology. The school is obliged to provide a forum for developing these competencies, eg extracurricular. Extracurricular field which has been developed is the field of Scientific Work of Youth (KIR). KIR much in demand by students. However, as long as this assistance is only focused on the pattern of writing and scientific writing course content. In fact, there are other indicators that determine, for example: a scientific presentation skills and communicative. Formulation of the problem in this activity is how the application of scientific presentation training to improve competitiveness in scientific writing competition for members of the KIR extracurricular in Semarang? This activity was conducted in SMA Negeri 2 Semarang, Friday, October 21, 2016. The training was attended by 30 participants. The activities carried out by the method of the workshop in the form of materials, modeling, discussion, practice, and assessment. The results of these highly optimized service programs in an understanding of the importance of scientific presentations competence. All participants started practicing continuous scientific presentations. They are also more confident in following various writing competitions. Keywords: scientific presentation, improve competitiveness in scientific writing competition